A Systematic Review of IFRS Sustainability Standards - Tharsika, K. (Institute of Certified Management Accountants of Sri Lanka, 2025)
Establishing the International Sustainability Standards Board (ISSB) by the IFRS Foundation marks a significant advancement in the standardisation of global sustainability-related disclosure. This study systematically reviews peer-reviewed literature from the Emerald database, concentrating on stakeholder responses, materiality discussions, implementation issues, and future direction concerns related to IFRS S1 and S2. The results underscore robust stakeholder endorsement of the ISSB’s objectives while causing significant apprehensions regarding legitimacy, inclusivity, and its singular materiality framework. The dominance of preparers in consultations and the insufficient representation from developing nations underscore power imbalances in standard- setting. Implementation problems encompass institutional power dynamics and possible misalignment with Sustainable Development Goals. The ISSB’s investor-centric methodology improves comparability, however its limited materiality breadth may compromise wider environmental and social goals. Future advancement hinges on the ISSB’s capacity to rectify legitimacy deficiencies, guarantee inclusive engagement, and integrate holistic sustainability viewpoints.
Keywords: IFRS S1 and S2; Materiality; Stakeholder response; Sustainability reporting; Sustainability Reporting Standard Board